The Great Exhibition
1 online resource (512 pages).
Keywords: The Great Exhibition of 1851 was the outstanding public event of the Victorian era. Housed in Joseph Paxton's Crystal Palace, it presented a vast array of objects, technologies and works of art from around the world. The sources in this edition provide a depth of context for study into the Exhibition.